Infusion of thinking skills in English language instructional development at tertiary level - Syed Aziz Baftim, Sharifah Sheha; Mustapha, Ghazali (Universiti Putra Malaysia Press, 2010)
The inclusion of thinking skills in a subject is considered necessary to ensure that students develop their thinking and possess greater control of their learning. To determine if the infusion of thinking skills is present in a subject, an evaluation of the subject from the planning to the assessment stage needs to be carried out. This study aims to evaluate the level of emphasis in the infusion of thinking skills in English language instruction in a Diploma Science program in a higher institution in Malaysia. A comprehensive study was carried out on the major stages of the instructional development based on Chen’s Taxonomy of Program Evaluation (2005). Specific data from documents was collected and analyzed, after the data was categorized according to the level of thinking skills listed in the Cognitive-Affective Taxonomy (Ghazali Mustapha, 1998) and the Mental Operation Questions (Moore, 1995). The three stages of the instructional development were then tied up to determine if they complement each other in the infusion of thinking skills. The quality of instruction provided will contribute to the success of the whole program, enabling students to possess equal opportunity to explore knowledge in depth and allowing them to apply it more effectively in the real world.